The translocator protein as a marker of macrophage and stromal activation in inflammatory arthritis: An initial investigation - Narayan, N; Carlucci, F; Dakin, S; Saleem, A; Sabokbar, A; Taylor, P (Oxford Academic, 2017)
TSPO is an 18kDa mitochondrial protein of indeterminate function. Its high expression on macrophages has led to its use as an imaging marker in inflammatory disease. Due to the critical role of macrophages in arthritis pathogenesis, TSPO may be useful as a marker of disease activity in inflammatory arthritis. Here, we demonstrate the TSPO PET (positron emission tomography) tracer [11C]PBR28 can detect and quantify synovitis. Through synovial histology, we demonstrate TSPO expression in tissue correlates with synovitis severity and macrophage prevalence. Little is known about the expression of TSPO in cells that constitute synovium. We present in vitro work demonstrating activated macrophages and fibroblasts highly express TSPO, hence may account for majority of tracer signal in joints imaged with TSPO targeted PET.